Analisis Akuntabilitas Perencanaan dan Anggaran Belanja (Studi Kasus Pada Kantor Badan Perencanaan Pembangunan, Penelitian, dan Pengembangan Daerah Kabupaten Sukabumi) - Rimawati, Anisa; Sulaeman, Sulaeman (Universitas Dian Nuswantoro, 2023)
This study aims to find out how the accountability of budget planning at the Regional Development Planning, Research and Development Agency (BAPPELITBANGDA) of Sukabumi Regency. The method used in this research is a qualitative method with a descriptive approach. Data collection tools used are observation, interviews, documentation and literature study. The results of this study are that the Office of the Development Planning, Research and Regional Development Agency (Bappelitbangda) of Sukabumi Regency is accountable or responsible for budget planning. It can be seen that Bappelitbangda